Bioconversion of Cellulosic Agricultural Wastes - Ajnavi, Somesh (My University, 2008)
Recycling of agricultural wastes comprising of garden waste (grass cutting) and leaf litter was carried out by different fungi (Aspergillus niger FS1 and Trichoderma reseei MTCC-164) and using cow dung and DAP (Di Ammonium Phosphate @ 0.1%) as activators. The results indicated that organic carbon was decreased from 28.6 % to 14.5% and cellulose from 534.4 ppm to 115.1 ppm, with concomitant increase in available nitrogen content and reducing sugars from 74.6 ppm to 356.5 ppm and from 117.7 ppm to 428.4 ppm respectively over 90 days of incubation. In garden waste cellulose was decreased by 77% and in leaf litter (comprising mainly with Bambusa vulgaris leaves) by 70 % when the biomass was treated with fungal consortia with the addition of 0.1% DAP as activator. The results indicated that activator like DAP enhances the rate of decomposition when agricultural wastes are either treated with fungal consortia or cow dung. In field conditions, the mixed agricultural waste was given hot water pretreatment at 80-90 ºC for 1 hour residence time to accelerate the degradation process over a period of 42 days. The results showed that organic carbon was decreased from 25.3% to 21.3% in hot water pretreated biomass. Available nitrogen in hot water pretreated biomass increased from 830 ppm to 1250 ppm, whereas in untreated biomass the increase was from 784 ppm to 1017 ppm. The cellulose degradation was also more pronounced in hot water pretreated biomass, it degraded to 57% from its initial concentration i.e., 365.1 ppm after 42 days of incubation. Reducing sugars also increased in hot water pretreated biomass as compared to the untreated one. The results indicated that the pretreatment had accelerated the degradation rate and led to an increase in nitrogen and reducing sugars as well as a decrease in organic carbon and cellulose.
M.Tech (Environment Science and Technology)
Keywords: cellulose; waste; bioconversion